Everything inside : stories - Danticat, Edwidge, 1969- (Alfred A. Knopf, 2019)
From the best-selling author of Claire of the Sea Light and Brother, I'm Dying, a long-awaited return to fiction: a gorgeous collection of stories about community, family and love; about the forces that pull us together or drive us apart--a book rich with vividly imagined characters, hard-won wisdom, and humanity. In these eight stories by widely acclaimed, prizewinning author Danticat--some of which have appeared The New Yorker--a romance unexpectedly sparks between two wounded friends; a marriage ends for what seems like noble reasons, but leads to irreperable consequences; a young woman holds on to an impossible dream, even as she fights for her life, two lovers reunite after the biggest tragedy in their country and in their lives. Vividly set in places from Miami to Port-au-Prince to a small unnamed country in the Caribbean and beyond, these beautiful and moving stories showcase one of the world's most renowned voices at her absolute best.